On the egg masses, eggs and embryos of Notocochlis isabelleana (D'orbigny, 1840) (Gastropoda: Naticidae) from Northern Patagonia - Pastorino, Roberto Santiago Guido (2009)
Naticids are common predators in sandy bottoms of shallow waters around the world. Probably due to their infaunal habitat, they are hard to find alive, particularly in the Patagonian waters of Argentina. Nevertheless, their presence is confirmed by the typical predation boreholes that can be seen on their bivalve prey along the coast (e.g., Bromley, 1981; Carriker, 1981; Pastorino & Ivanov, 1996; Signorelli et al., 2006). These boreholes record information on predators without actually seeing them. Paleontologists have exploited this field, analyzing the behavior and producing models of predator-prey relationships in ancient and recent communities (Kabat, 1990, and citations herein).